2023
DOI: 10.1101/2023.04.27.537858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The first two chromosome-scale genome assemblies of American hazelnut enable comparative genomic analysis of the genusCorylus

Abstract: The native shrub American hazelnut (Corylus americana) is currently used in breeding programs that are aiming to develop commercially viable hazelnut varieties for the U.S. Upper Midwestern U.S. This species provides significant ecological benefits as it is a perennial crop and well-adapted to this region. Breeding cycles for perennial species are long, and may benefit from the use of predictive methods such as genomic selection to reduce cycle time and increase the efficiency of field trials. High-quality ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…Expression analyses and yeast two-hybrid assays confirmed that Corylus does not employ the SRK-mediated signaling pathway of Brassica SSI ( Hill et al., 2021 ; Hou et al., 2022a , 2022b ). Recent phylogenetic analysis provided additional evidence supporting the genus-specific evolution of SSI in Corylus , which is not shared by other members of Betulaceae ( Brainard et al., 2023 ).…”
Section: Molecular Basis Of Self-pollen Rejection In Different Si Sys...mentioning
confidence: 99%
“…Expression analyses and yeast two-hybrid assays confirmed that Corylus does not employ the SRK-mediated signaling pathway of Brassica SSI ( Hill et al., 2021 ; Hou et al., 2022a , 2022b ). Recent phylogenetic analysis provided additional evidence supporting the genus-specific evolution of SSI in Corylus , which is not shared by other members of Betulaceae ( Brainard et al., 2023 ).…”
Section: Molecular Basis Of Self-pollen Rejection In Different Si Sys...mentioning
confidence: 99%